Advanced triage to redirect non-urgent Emergency Department visits to alternative care centers: the PERSEE algorithm. Issue 3 (4th May 2022) - Gilbert, Allison; Brasseur, Edmond; Petit, Mérédith; Donneau, Anne Françoise; D'Orio, Vincent; Ghuysen, Alexandre
ABSTRACT: Objectives: Primary care treatable visits in the Emergency Department (ED) are part of the different factors leading to the overcrowding. Their triage and diversion to alternative care centers could potentially help manage the increasing inflow provided the establishment of an advanced triage to ensure patients' safety. We aim to suggest a new triage tool, PERSEE, and prove its feasibility, safety and performance. Methods: All self-referrals presented to the ED were triaged with the PERSEE algorithm: first, patients were classified with a five-level ED acuity scale and then evaluated by algorithms to determine their appropriate category (ED or Primary Care). Patients were eligible for a redirection if they were triaged by the acuity scale as level 3 or lower, considered as ambulatory patients and finally categorized as primary care patients. We defined appropriate redirections as patients requiring less than three emergency resources, no emergency-specific treatment and no hospitalization. Results: During the study, 1999 patients were admitted to the ED. Among those, 1333 patients were self-referred (66.9%) of whom 1167 patients were triaged as level 3 or below (58.6%) and 775 patients triaged as ambulatory (39.0%). Among the 775 patients, 200 patients were categorized as primary care treatable (10.0%) and thereby, as potentially eligible for a redirection. We noticed an error rate of 7%, sensitivity of 24.06% and specificity of 97.6%. The redirection rate reached 15% of the self-referrals. Conclusion: These results indicate that PERSEE triage could lead to a safe redirection and could be an efficient tool to reduce ED crowding provided several adjustments.